Evaluación del riesgo de la morosidad de cartera vencida en la Cooperativa de Ahorro y Crédito “San Antonio” del Cantón Vinces durante el periodo 2022. - León Barros, José Francisco (2023)
This study focuses on evaluating the delinquency risk in the overdue credit portfolio of Savings and Credit Cooperative San Antonio during the year 2022, with the purpose of determining its impact on the financial institution's profitability. The problem statement arises from the growing concern about the increase in delinquency in the cooperative and its repercussion on the loan recovery capacity, which can significantly affect its financial health. The justification for conducting this research is based on the importance of addressing delinquency in a financial institution that largely relies on credit loans as a source of income. Delinquency not only affects the liquidity of the cooperative but can also require additional financing methods to offset the losses, making it essential to thoroughly understand its causes and effects. The general objective is to assess the delinquency risk in the overdue credit portfolio during the year 2022 to determine its impact on the profitability of Savings and Credit Cooperative San Antonio. To achieve this, a mixed methodology that combines quantitative and qualitative approaches will be employed, including the review of internal policies and practices, financial statement analysis, and the identification of key performance indicators. As a result of this research, it is expected to provide recommendations that strengthen risk management and delinquency prevention in the cooperative, aiming to maintain its financial health and effectively meet the needs of its members and clients